Implementasi Teknologi Informasi Website Pada Home Industry Sebagai Media Promosi Dan Penjualan (Studi Kasus: Usaha Roti Dapoer Yuri): Teknologi Informasi - Rosiska, Evan (Universitas Putera Batam, 2020)
The development of information technology that exists today has made people's lifestyles much easier. In selling the products sold at the Dapoer Yuri Bread Business, they still apply a conventional system, the marketing strategy is carried out directly by delivering products to stalls, shops and even some consumers who come directly to the house to pick up these products . Meanwhile, the current promotional media only takes advantage of consumers who have bought the bread, this makes sales less effective and promotions that are not widely known by many people. When viewed from the development of information system technology that is currently developing, Dapoer Yuri's Bread Business really needs a technology to increase sales and as a product promotion media that can be accessed online and can be accessed anywhere and anytime, where buyers are able to find information on products to be sold and carry out online ordering transactions. The research method used is the waterfall model, namely through several stages such as needs analysis, system design, program code and system testing. In completing the data so that the objectives can be achieved, the data collection techniques use observation and study techniques. Meanwhile, the results of the implementation of this information technology are able to provide increased sales and easier promotion.